Linguistic Branding: The Role of Word Formation in TikTok Branding - Batrisya Amalia Putri; Devian Try Gustary; Aam Alamsyah (Merwinspy Publisher, 2025)
This study investigates the intersection of word formation and personal branding on social media, focusing on the content of a Gen Z TikTok creator named Jazzy. As TikTok serves as a dynamic platform for linguistic innovation, this research explores how a creator's language choices contribute to their digital persona. Employing a qualitative descriptive method with a morphological approach, the study analyzes five of Jazzy's most popular self-development videos. In this study, the researcher acts as the main instrument, supported by observation and note-taking techniques. The data were collected from five of Jazzy’s most-viewed TikTok videos through qualitative observation. The linguistic data were then analyzed descriptively by identifying word formation processes based on McCarthy’s (2002) theory and interpreting their relation to Rampersad’s (2008) personal branding framework. The findings reveal that compounding and derivation are the most frequently used word formation types, strategically utilized to build her brand. These linguistic choices directly support key personal branding elements, particularly specialization and authenticity. In conclusion, the study finds that linguistic creativity is not merely a reflection of online culture but a powerful, strategic tool for identity construction and audience engagement. This contributes to a broader understanding of how language and communication evolve within the context of digital media.